الرسائل الأدبیة عند التاكُرُنّي دراسة أسلوبیة - أ.م.د. فاطمة حیدر علي (College of Education for Women, 2019)
Stop the search on the performance of the stylistic literary messages sent by Abu Mohammed Amer bin Said Altakrna to the kings of his time and Ullach highlighting the method of the three levels is psychological and away the consignee and the receiver Taster literary text. Level voice and rhythmic, which dealt with (alliteration and Naturalization voice, and repetition and parallelism, and rhyme and toning) and its impact on the taste and the emotional art between the sender and the receiver Bashklah. Who has studied the structural level (introductory sentence order methods in the messages, generally have much style presentation and brief delays and actor, and then end the moral and intellectual martyrdom and desalination hair or Altersl him and with him the importance of correlation. The semantic level. Studied metaphor and simile and metaphor and images intensive in order to influence the recipient. Find out and telegraphic messages and Altakrna Ffinetha high as well as the motives and purposes of the public to send these messages, which according to news addressee interest and influence as reported by the insider and a researcher on art and creativity rhetorical.